Endogenous economic growth as a condition of modernization of Russia's economy - V M Matushok; S A Balashova (RUDN Journal of Economics, 2010)
Today the most important factors for long-term economic growth is not only labor and large stocks of physical capital but human capital investment, high government spending in infrastructure and basic research, innovation, combined behavioral and institutional parameters. This conclusion is also supported by the modification of the econometric Makarov-Ayvazian model, using which examines the dynamics of macroeconomic indicators of Russia as a result of the interaction of endogenous and exogenous factors. Scenario calculations show that even without considering the impact of the current economic crisis, maintaining fixed capital investment at the same level will lead to stagnation and stop growth. At the same time, increasing investment and public spending, but the same pace, while maintaining their low returns, is leading to slower economic growth. To modernize the economy an appropriate institutional environment is necessary, in the presence of which all factors are beginning to generate an endogenous, self-sustaining growth.